Exact symbol error probability of orthogonal space-time block codes - Gharavi-Alkhansari, M.; Gershman, A.B. (2003 37th Asilomar Conference on Signals, Systems and Computers, 2003)
In this paper, we obtain simple exact expressions for the average error probability at the output of the maximum likelihood (ML) decoder in the general case of arbitrary orthogonal space-time block code (OSTBC) and input signal constellations. Such expressions are derived for random uncorrelated Rayleigh/Rician fading channels and both the cases of two- and higher-dimensional signal constellations.